Corporate social responsibility : academic insights and impacts - Vertigans, Stephen; Idowu, Samuel O. (Springer International Publishing : Imprint : Springer, 2017)
This work collects the most important results presented at the Congress on Differential Equations and Applications/Congress on Applied Mathematics (CEDYA/CMA) in Cádiz (Spain) in 2015. It supports further research in differential equations, numerical analysis, mechanics, control and optimization. In particular, it helps readers gain an overview of specific problems of interest in the current mathematical research related to different branches of applied mathematics. This includes the analysis of nonlinear partial differential equations, exact solutions techniques for ordinary differential equations, numerical analysis and numerical simulation of some models arising in experimental sciences and engineering, control and optimization, and also trending topics on numerical linear Algebra, dynamical systems, and applied mathematics for Industry. This volume is mainly addressed to any researcher interested in the applications of mathematics, especially in any subject mentioned above. It may be also useful to PhD students in applied mathematics, engineering or experimental sciences.
Keywords: Social responsibility of business.; Business ethics.; International business enterprises -- Moral and ethical aspects.; International business enterprises -- Environmental aspects.; Corporations -- Environmental aspects.; Corporations -- Sociological aspects.; Globalization -- Moral and ethical aspects.; Globalization -- Environmental aspects.; Environmental management.; Economics -- Sociological aspects.; elektronické knihy; electronic books